PERAN ORANG TUA DALAM MEMOTIVASI ANAKUNTUK MELANJUTKAN PENDIDIKAN KE PESANTREN(Studi di Desa Lela, Kecamatan Teluk Keramat Tahun 2025) - Sarfika; Hifza; Jeprianto (CV. ADIBA ASIHA AMIRA, 2026)
This study aims to analyze (1) the role played by parents for children who will continue their education to Islamic boarding schools; (2) the approach of parents in motivating children to continue their education to Islamic boarding schools; (3) the methods of parents in motivating their children to continue their education to Islamic boarding schools. Data collection techniques used observation, interviews, and documentation. Data analysis techniques were carried out through data collection, data reduction, data presentation, and drawing conclusions. The research results indicate that (1) Parents play a very important role in shaping a child's motivation to continue education at an Islamic boarding school. This role is manifested through being an educator, inspirer, motivator, facilitator, mentor, and communicator. Parents instill an understanding of the importance of religious education, provide examples in daily life, offer emotional support, and provide facilities that support the child's education. In addition, parents also build open and effective communication and accompany the child in making decisions. (2) The approaches used by parents include emotional approaches, communicative approaches, and role modeling that are applied continuously in daily life. (3) The methods used by parents include advice, exemplary behavior, habituation, providing support and reinforcement, as well as storytelling methods. These methods are able to foster awareness, mental readiness, and intrinsic motivation in children in determining their choice of education in Islamic boarding schools. The success of motivating children is greatly influenced by the consistent and continuous involvement of parents.